Determination of The Effect of Technological Procedures Applied in Feed Factories on Mixed Feed Nutrition and Forming Quality Critical Points - Yavuz Gürbüz; Mustafa Yılmaz (Turkish Journal of Agriculture: Food Science and Technology)
In this study, it is aimed to establish quality critical points in order to determine the quality of feeds prepared in compound feed factories before production. For this purpose, quality control points should be established and continuously monitored in compound feed production. With our study, the quality of the raw materials we use in the production of compound feed (feed nutrient contents), and then determined the important technological changes in feed mill; control points were established in mill, mixer, molasses mixer, conditioning, pellet press inlet, pellet press outlet, cooler and packaging sections. Four different mixed feeds (quail, laying hens, dairy cow, beef cattle feed) were sampled from these regions. The study was carried out in a commercial feed factory. Firstly, rations were prepared with the formulation program on the computer of these compound feeds. Then, samples were taken from the determined points and nutrient contents (dry matter, crude protein, crude oil, crude cellulose, crude ash, starch, sugar, metabolic energy value) were compared with both chemical and NIRS method. According to the data obtained; In the samples taken under the mill, both chemical and NIRS methods were used and the results did not reflect the formulation values. According to the findings of the research, the results obtained from the samples taken from the sub-mixer bunker showed close values from the formulation values of the mixed feeds and it was concluded that it may be the most appropriate quality critical point.